Shaping global agendas on climate risk management and climate services: an IRI perspective - Hansen, James; Zebiak, Stephen E.; Coffey, Kevin (Springer, 2014)
This paper provides a historical overview of the development and mainstreaming of global agendas on climate risk management and climate services from the vantage point of the International Research Institute for Climate and Society (IRI), and present two examples that illustrate how efforts to mainstream these agendas shaped both the institute and the broader communities that it sought to engage. In the first example, we trace developments that led to the emergence of a global agenda on climate services, including creation of the Climate Services Partnership (CSP). The CSP is an informal, open network of interested climate information users, providers, donors and researchers, serves as a platform for knowledge sharing and collaboration to advance climate service capabilities worldwide. The second example is mainstreaming climate risk management within the international agricultural research-for-development community. The CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS) was structured to include a research theme on “Adaptation through Managing Climate Risk,” which put climate risk management on the same footing within the agenda as adaptation to future climate change. We conclude with several lessons drawn from IRI’s involvement in the processes that shaped global agendas around climate risk management and climate services.